Research on Modified Structure of Turbo-Blast System - Wang Rui; Wang He; Fan Chen; Zhang Xin; Yang Dacheng (2006 IEEE 17th International Symposium on Personal, Indoor and Mobile Radio Communications, 2006)
In this paper, a new MIMO system named turbo-BLAST which utilizes the turbo principle is investigated. Meanwhile, we propose the idea of using advanced channel codes in the system , such as turbo code and TCM (trellis code modulation) code. New algorithm of detector is deducted in order to fit for non-constant envelope modulation. There new structures are proposed: a modified structure named selective feedback are proposed to reduce the time-delay of turbo-BLAST for high-order modulation, the decoding algorithm of trellis code modulation is modified to provide the detector with extrinsic information, and the new decoder structure of turbo code is also given. The simulation results show that selective feedback can achieve better performance, and the structure using turbo code can achieve better performance and faster convergence rate in high-order modulation